Hansenomysis sorbei n. sp., a new suprabenthic mysid (Crustacea: Mysida: Petalophthalmidae) from the Bellingshausen Sea (Southern Ocean) - San Vicente, Carlos (Zootaxa, 2009)
A new Petalophthalmidae mysid, Hansenomysis sorbei n. sp., is described from specimens sampled with a suprabenthic sled in the Bellingshausen Sea (Southern Ocean). Hansenomysis sorbei is distinguishable from its closest congener, H. carinata Casanova, 1993, by the carapace and abdominal somites sculpturing and the relative size of uropods and telson. This new species is the fifth Hansenomysis species described from the Southern Ocean. An identification key for the Antarctic and Subantarctic Hansenomysis species is also included.